A Method for Fast Assessment of OP/CB Exposure in the Japanese Quail (Coturnix coturnix japonica) Using Combined Esterases Enzyme Activity as Biomarkers. (9th January 2014) - Abass, Kasim Sakran
Abstract : The aims of this study were to investigate the presence of different esterase activities in plasma and liver for Japanese quail and to combine determination of both carboxylesterase and cholinesterase as biochemical biomarker in order to identify the effects of carbamate and organophosphate compounds exposure. Carboxylesterase exhibits larger sensitivity to carbamate and organophosphate compounds than to cholinesterase and is present at higher levels. This permitted nature and distribution of carboxylesterase or cholinesterase to be measured. One predominant toxicological form of enzyme level constant in its patterns of motivation and inhibition with cholinesterase was identified in plasma with an apparent Michaelis constant for butyrylthiocholine iodide of 0.394 mM. Carboxylesterase activity in liver was considered by its preferential hydrolysis of the S-phenyl thioacetate. A concentration dependent decrease of carboxylesterase and cholinesterase has demonstrated during in vitro incubation of malathion, parathion, and trichlorfon in the range 0.125–2 mM, while with methomyl was in the range 0.25–4 mM. When quail (n = 15 ) was exposed orally for 48 h to concentrations of carbamate or organophosphate compounds of 3–200 mg/kg, the percentage inhibition of cholinesterase was in each case larger than that of carboxylesterase and reached statistical significance (P < 0.05 ) at lower concentrations.